Dampak Pertumbuhan Penjualan, Leverage, Ukuran Perusahaan, dan Profitabilitas Terhadap Cash Holding - Sufiyati Sufiyati; Liana Susanto; Sofia Prima Dewi; Merry Susanti (Jurnal Bina Akuntansi, 2022)
This study aims to determine whether sales growth has a negative impact on cash holding,whether leverage has a positive impact on cash holding, whether company size has a positiveimpact on cash holding, and whether profitability has a positive impact on cash holding. Thepopulation is a manufacturing company that is consistently listed on the Indonesia StockExchange during 2016-2019. Purposive sampling was used as a sampling technique. The datais processed using EVIEWS. This study shows that sales growth has a negative impact oncash holding, leverage does not have a positive impact on cash holding, firm size does nothave a positive impact on cash holding, and profitability does not have a positive impact oncash holding.